(untitled) (Analysis in Theory and Applications, 2013)
This paper is concerning the commutators generated by the multilinear singular integral with rough kernels and BMO functions. The boundedness of the multilinear commutators T_b (f) is established on the Morrey-Herz space by using the John-Nirenberg inequality.